Endoscopy in Small Bowel Diseases 2021
DOI: 10.5772/intechopen.96435
|View full text |Cite
|
Sign up to set email alerts
|

Early Recognition and Management of Small Bowel Perforation

Abstract: Enteroscopy has a procedure-related perforation rate from less than 1% to 6.5%. It seems to be higher in therapeutic enteroscopy, especially polypectomy of large polyps, and in patients who have altered surgical anatomy. Early recognition is life-saving and studies have shown that if surgery is done within 12 hours of perforation the prognosis is better. In a patient who has undergone small bowel endoscopy the diagnosis of small bowel perforation should be suspected if the patient has acute pain in the abdomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This is following the results of a study in Turkey involving 576 appendicitis patients which showed that the group of perforated appendicitis was dominated by the male sex, but there was no significant difference between men and women in the statistical test of both groups. 7 In the bivariate analysis between increased levels of lactic acid in patients with acute appendicitis and perforation, the p-value> 0.05 (p=0.14; OR:1.07; 95%CI: -0.03-0.22) It means that were no significant results between the increase in the value of lactic acid with the severity of appendicitis. These results were strengthened by the correlation analysis of lactic acid values and the severity of appendicitis, the Pearson Correlation value was 0.186, which means the correlation was very weak.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This is following the results of a study in Turkey involving 576 appendicitis patients which showed that the group of perforated appendicitis was dominated by the male sex, but there was no significant difference between men and women in the statistical test of both groups. 7 In the bivariate analysis between increased levels of lactic acid in patients with acute appendicitis and perforation, the p-value> 0.05 (p=0.14; OR:1.07; 95%CI: -0.03-0.22) It means that were no significant results between the increase in the value of lactic acid with the severity of appendicitis. These results were strengthened by the correlation analysis of lactic acid values and the severity of appendicitis, the Pearson Correlation value was 0.186, which means the correlation was very weak.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies in patients with perforated appendicitis found higher plasma levels of lactic acid than in patients with acute nonperforated appendicitis (96% sensitivity; 87% specificity). 7 Research in Indonesia on lactic acid biomarkers as a risk predictor of perforated appendicitis is rare and currently has not been done in Bandung. The researcher intends to find out the correlation between lactic acid values as a predictor of perforated appendicitis in adult patients who had been previously diagnosed with acute appendicitis in Dr. Hasan Sadikin General Hospital Bandung, Indonesia.…”
Section: Introductionmentioning
confidence: 99%